MODEL KOMUNIKASI PEMBANGUNAN DALAM PROGRAM STRATEGIS PEMBANGUNAN EKONOMI DAN KELEMBAGAAN KAMPUNG - Abdul Qadir; Teddy Khumaedi (Program Studi Komunikasi dan Penyiaran Islam, 2022)
Development Communication Model In Strategic Development Program Economist idan Institutional Kampung (PROSPEK) In Enggros Villung Village Abepura District Jayapura City, This research is motivated by strategic program of economic development and institutional of kampung (Prospek) conducted in Papua Province in the year 2014. Particularly in Enggros Village. The purpose of this research is to know the development communication model in the prospect used for the successful implementation of Prospect in Kampung Enggros. The method used is descriptive method with qualitative research form. Based on the result of research indicate that the development communication model in Prospect in Kampung Enggros starts from planning stage, implementation stage, utilization of result, and stage of controlling, monitoring and evaluation. While the development communication model used is; persuasive communication model, model and dialogical communication